Fused fluorenylindolenine-donor-based unsymmetrical squaraine dyes for dye-sensitized solar cells - Bisht, Rajesh; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Karjule, Neeta; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
A series of four unsymmetrical squaraine dyes, XSQ1-4, were synthesized using a fused fluorenylindolenine-based donor unit for dye-sensitized solar cells (DSSCs). The fused structure of fluorenylindolenine helped in moving the absorption toward the near-infrared (NIR) region, and the two sp(3)-C centers available on this donor were utilized to incorporate out-of-plane alkyl chains in opposite directions to control the dye-dye interactions on the TiO2 surface. High extinction coefficient (epsilon >= 10(5) M-1 cm(-1)) for absorbing NIR photons and suitable highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels with respect to the conduction band of TiO2 and electrolyte for charge injection and dye regeneration processes, respectively, make these dyes potential sensitizers for DSSCs. Introduction of branched alkyl groups in the pi-framework helped in controlling dye aggregation to reduce exciton quenching and assisted in TiO2 surface passivation to avoid the charge recombination process. Furthermore, having a naphthyl group on the indole part of the anchoring group containing segment helped to red-shift the absorption spectrum of dyes 15 nm toward the NIR region (XSQ3-4). Among all of the dyes under investigation, XSQ2 gave the best photovoltaic performance, having a short-circuit current density (J(SC)) of 13.99 mA cm(-2), open -circuit voltage (V-OC) of 0.66 V, and a fill factor (ff) of 0.71, with a device performance (eta) of 6.57%. Electrochemical impedance spectroscopy revealed higher electron lifetime on TiO2 for XSQ2, which helps to avoid the charge recombination process.
Keywords: Dye-sensitized solar cells; fluorenylindolenine; H- and J-type aggregation; NIR absorption; out-of-plane alkyl groups; squaraine dyes

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye